Institutional Knowledge, Human Capital, and Accounting Technology Adoption: Explaining Financial Reporting Quality under Environmental Uncertainty - Intan Permata Islami; Shinta Melzatia (KOMUNITAS: Jurnal Ilmu Sosiologi, 2026)
This study examines how institutional knowledge, human capital, and accounting technology adoption shape the financial reporting quality of Micro, Small, and Medium Enterprises (SMEs) under conditions of environmental uncertainty. Grounded in economic and organizational sociology, the research conceptualizes financial reporting not merely as a technical outcome but as a socio-institutional practice formed through the interaction between actor capacity and institutional structures. A quantitative causal design was employed using survey data collected from 100 SMEs in Bekasi City, Indonesia, in 2025 through stratified random sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that accounting information technology utilization, human resource competence, and understanding of SME Financial Accounting Standards (SAK EMKM) each have a positive and significant effect on financial reporting quality. Environmental uncertainty does not moderate the relationship between technology utilization and reporting quality; however, it weakens the effect of human competence while strengthening the influence of institutional accounting knowledge. These results suggest that financial reporting quality depends not only on digital adoption and individual capability but also on the internalization of institutional standards, particularly in unstable business environments. The study’s novelty lies in integrating technological, human capital, and institutional perspectives within a contingency framework of environmental uncertainty, contributing to debates in economic and organizational sociology on how accounting practices are socially embedded in SME governance.